Crataegus L. туўысы түрлериниң биоэкологиясы ҳәм хожалық әҳмийети - Отенова, Ф.Т; Нурмахашева, Г.С. Crataegus L (SCIENCE and SOCIETY, 2018)
The article deals with the history of introduction of Сrataegus L. in Karakalpakstan, its bioecological peculiarities as well as its role in agriculture.
Keywords: Сrataegus L; introduction; green zone; bioecology; features; decorative; medicinal; economic importance